Effect of air pollution on the global burden of cardiovascular diseases and forecasting future trends of the related metrics: a systematic analysis from the Global Burden of Disease Study 2021 - Mao, Qingsong; Zhu, Xiaoyi; Zhang, Xinyi; Kong, Yuzhe (Frontiers in Medicine, 2024)
This study assesses the worldwide cardiovascular disease (CVD) burden attributed to air pollution, utilizing data from the Global Burden of Disease Study 2021.We explored the impact of air pollution on CVDs globally, regionally, and nationally, while considering correlations with age, gender, and Socio-Demographic Index (SDI). A decomposition analysis was conducted to discern the contributions of aging, population growth, and epidemiological shifts to the changes in Disability-Adjusted Life Years (DALYs) from 1990 to 2021. Additionally, an ARIMA model was used to forecast the future CVD burden through 2050.In 2021, air pollution was responsible for approximately 2.46 million deaths and 58.3 million Disability-Adjusted Life Years (DALYs) attributable to CVDs, with a discernible decrease over the period studied.The greatest impacts were observed in individuals aged 75-79 and over 80, particularly among males. The decomposition analysis indicated that shifts in epidemiology were the primary factors driving these changes. Future projections suggest potential increases in mortality and DALY rates in regions with low and high-middle SDI, alongside rising age-standardized death and mortality rates in high SDI areas.These findings underscore the urgency of implementing targeted CVD prevention and air pollution control strategies to mitigate the impact on public health.